(RESISTANCE OF Lactobacillus spp. FBB TO SIMULATION OF UPPER PART INTESTINAL TRACT CONDITION FOR PROBIOTIC DEVELOPMENT) - Ida Ayu Sri Sinca Maha Uni; Yan Ramona; I Nengah Sujaya (ARCHIVE OF COMMUNITY HEALTH, 2013)
Lactobacillus spp. FBB (isolates 60, 72, dan 75), isolated from feces of healthy infants, were tested for resistance in a modified gastric juice in vitro, before being applied in in vivo tests. These isolates were exposed for 7 hours in the modified gastric juice (added with pepsin, pancreatin, and NaDC) with various pH of 2, 3, 4, or 8. Isolates of FBB that showed the most resistant properties in this test was identified by applying molecular method or by sequencing its 16S rDNA. In this test, the FBB isolates showed various degree of resistance to the modified gastric juice conditions. FBB72 was found to be more resistant than the two other isolates. This isolate appeared to have the ability to reach colon (viable when reach colon), although its density was very low (104 CFU/ml and 103 CFU/ml at pH 4 and 3, respectively). Based on its 16s rDNA nucleotide sequence, this FBB72 was found to be closely related to Lactobacillus rhamnosus GG ATTCC53103 with 99% similarity.